EVALUASI ETOS KERJA, MOTIVASI, KOMPETENSI, KAPABILITAS, DAN INTEGRITAS ANGGOTA KOPERASI RUMPUT LAUT (Gracilaria sp.) AGAR SENTOSA MAKMUR, KABUPATEN SIDOARJO - Tryono, Agus; Istiqomah, Titis; Soedrijanto, Angky; Mustofa, Mustofa (Jurnal Perikanan Pantura (JPP), 2026)
The work behavior of seaweed cooperative members must reflect high performance. As one of Indonesia’s strategic national commodities currently being promoted by the government, seaweed must be able to compete as a high-quality export product in the global market. This study aims to evaluate the performance of seaweed cooperative members (Gracilaria sp.) in terms of developing work ethic, motivation, competence, capability, and integrity in seaweed cultivation in Sidoarjo Regency. This research is a descriptive study using an empirical survey approach conducted on members of the Agar Sentosa Makmur Seaweed Cooperative in Sidoarjo Regency. Data were collected through in-depth interviews. The interview results were weighted on a scale of 1–10 and analyzed using statistical tools to determine correlations among the studied variables. The results indicate that the capability of cooperative members in seaweed cultivation is relatively high. However, this level of capability still needs to be balanced by improving their competence.